How culture modulates anthropomorphism in Human-Robot Interaction: A review - Cecilia Roselli; Leonardo Lapomarda; Edoardo Datteri (Acta Psychologica)
Anthropomorphism is the tendency to attribute human-like characteristics to nonhuman agents, including robots. In the context of Human-Robot Interaction (HRI) research, it is relevant to understand what factors are at play in modulating individuals' anthropomorphism towards robots. This literature review addresses whether and how people's culture, which we identified as a potential factor of interest, affects their tendency to attribute anthropomorphic traits to robots. Moreover, we sought to determine whether the presence (or absence) of a relationship between culture and anthropomorphism towards robots varies as a function of i) the definition of both culture and anthropomorphism and ii) methodological factors, such as the measurements of culture and anthropomorphism adopted in the reviewed studies, as well as participants' and robot's characteristics. In most of the studies we reviewed, we observed a relationship between culture and anthropomorphism, i.e., individuals' cultural profile significantly affects how and how much they attribute anthropomorphic traits to robots. However, the directionality of the relationship is not consistent across studies. Furthermore, there is a small number of reviewed studies that showed a lack of relationship between culture and anthropomorphism towards robots. Although our findings do not vary as a function of the theoretical and methodological factors we identified, results are mixed, probably due to the large variability in those methods. The review contributes to extending current knowledge regarding the impact of individuals' culture on anthropomorphism towards robots, and provides suggestions towards a more controlled and rigorous investigation of the phenomenon.